ARNO is recruited by the neuronal adaptor FE65 to potentiate ARF6-mediated neurite outgrowth. Issue 9 (28th September 2022) - Zhai, Yuqi; Chan, Wai Wa Ray; Li, Wen; Lau, Kwok-Fai
Abstract : Abstract : ADP-ribosylation factor 6 (ARF6) is a small GTPase that has a variety of neuronal functions including stimulating neurite outgrowth, a crucial process for the establishment and maintenance of neural connectivity. As impaired and atrophic neurites are often observed in various brain injuries and neurological diseases, understanding the intrinsic pathways that stimulate neurite outgrowth may provide insights into developing strategies to trigger the reconnection of injured neurons. The neuronal adaptor FE65 has been shown to interact with ARF6 and potentiate ARF6-mediated neurite outgrowth. However, the precise mechanism that FE65 activates ARF6 remains unclear, as FE65 does not possess a guanine nucleotide exchange factor (GEF) domain/function. Here, we show that FE65 interacts with the ARF6 GEF, namely the ARF nucleotide-binding site opener (ARNO). Moreover, a complex consisting of ARNO, ARF6 and FE65 is detected. Notably, FE65 potentiates the stimulatory effect of ARNO on ARF6-mediated neurite outgrowth, and the effect of FE65 is abrogated by an FE65 mutation that disrupts FE65–ARNO interaction. Additionally, the intramolecular interaction for mediating the autoinhibited conformation of ARNO is attenuated by FE65. Moreover, FE65 potentiates the effects of wild-type ARNO, but not the monomeric mutant, suggesting an association between FE65 and ARNO dimerization. Collectively, we demonstrate that FE65 binds to and activates ARNO and, consequently, potentiates ARF6-mediated neurite outgrowth.